Xiphopagic conjoined twins: A case report with pre and postnatal imaging - Jottrand Z; Geeraerd F; D'Hondt A; Donner C; Avni FA (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2023)
Siamese or conjoined twins represent a rare but specific malformation occurring in monozygotic and mono-amniotic twin pregnancies. We report a case of xiphopagic conjoined twins and compare the contribution and correlation between ante- and post-mortem imaging for the detailed evaluation of the malformation. Our case highlights the importance of postnatal imaging to better understand this complex type of fetal malformation.